Klotho as Potential Autophagy Regulator and Therapeutic Target - Zhou, Hongjing; Pu, Shiyun; Zhou, Houfeng; Guo, Yuanxin (Frontiers in Pharmacology, 2021)
The protein Klotho can significantly delay aging, so it has attracted widespread attention. Abnormal downregulation of Klotho has been detected in several aging-related diseases, such as Alzheimer’s disease, kidney injury, cancer, chronic obstructive pulmonary disease (COPD), vascular disease, muscular dystrophy and diabetes. Conversely, many exogenous and endogenous factors, several drugs, lifestyle changes and genetic manipulations were reported to exert therapeutic effects through increasing Klotho expression. In recent years, Klotho has been identified as a potential autophagy regulator. How Klotho may contribute to reversing the effects of aging and disease became clearer when it was linked to autophagy, the process in which eukaryotic cells clear away dysfunctional proteins and damaged organelles: the abovementioned diseases involve abnormal autophagy. Interestingly, growing evidence indicates that Klotho plays a dual role as inducer or inhibitor of autophagy in different physiological or pathological conditions through its influence on IGF-1/PI3K/Akt/mTOR signaling pathway, Beclin 1 expression and activity, as well as aldosterone level, which can help restore autophagy to beneficial levels. The present review examines the role of Klotho in regulating autophagy in Alzheimer’s disease, kidney injury, cancer, COPD, vascular disease, muscular dystrophy and diabetes. Targeting Klotho may provide a new perspective for preventing and treating aging-related diseases.